Anxiety and Suicidal Thoughts During the COVID-19 Pandemic: Cross-Country Comparative Study Among Indonesian, Taiwanese, and Thai University Students - Pramukti, Iqbal; Strong, Carol; Sitthimongkol, Yajai; Setiawan, Agus; Pandin, Moses Glorino Rumambo; Yen, Cheng-Fang; Lin, Chung-Ying; Griffiths, Mark D; Ko, Nai-Ying (Journal of Medical Internet Research, 2020)
BackgroundThe COVID-19 pandemic has negatively affected the mental health of university students. ObjectiveThis study examined the psychological responses toward COVID-19 among university students from 3 countries—Indonesia, Taiwan, and Thailand. MethodsWe used a web-based, cross-sectional survey to recruit 1985 university students from 5 public universities (2 in Indonesia, 1 in Thailand, and 1 in Taiwan) via popular social media platforms such as Facebook, LINE, WhatsApp, and broadcast. All students (n=938 in Indonesia, n=734 in Thailand, and n=313 in Taiwan) answered questions concerning their anxiety, suicidal thoughts (or sadness), confidence in pandemic control, risk perception of susceptibility to infection, perceived support, resources for fighting infection, and sources of information in the context of the COVID-19 pandemic. ResultsAmong the 3 student groups, Thai students had the highest levels of anxiety but the lowest levels of confidence in pandemic control and available resources for fighting COVID-19. Factors associated with higher anxiety differed across countries. Less perceived satisfactory support was associated with more suicidal thoughts among Indonesian students. On the other hand, Taiwanese students were more negatively affected by information gathered from the internet and from medical staff than were Indonesian or Thai students. ConclusionsOur findings suggest that health care providers in Thailand may need to pay special attention to Thai university students given that high levels of anxiety were observed in this study population. In addition, health care providers should establish a good support system for university students, as the results of this study indicate a negative association between support and suicidal thoughts.